Quality changes of edible oils during vacuum and atmospheric frying of potato chips. (December 2022) - Manzoor, Shaziya; Masoodi, F.A.; Rashid, Rubiya; Ganaie, Tariq Ahmad
Abstract: Demand for safe and nutritionally rich fried products is gaining a momentum among consumers, leading to the increased consumption of vacuum fried products. The impact of vacuum frying (VF)(110 °C, 40 kPa) on chemical composition of food, fatty acid profile, microstructure, oxidative stability and sensory attributes was assessed and differentiated with that of atmospheric frying(AF) (180 °C). The potato slices were fried in mustard and soyabean oil used repetitively for 25 h. The oil content of VF potato chips was lower (15.18%) than AF chips (18.98%), however water loss in AF chips was higher than VF chips by 1.63-fold. VF significantly prevented the PUFA degradation, minimizes transfatty acid (TFA) formation and maintain a low C18:2/C16:0 ratio as compared to AF. VF Chips fried in soyabean oil show an increase in TFA content from 2.15 to 2.63% and a decrease in PUFA from 51.57 to 45.16% as compared to AF chips where TFA content increased from 2.15 to 3.72% and PUFA shows a higher reduction from 51.57 to 37.69% at the end of 25 h of frying. This indicate that in AF, oil is safe for use upto 10 cycles of frying, while as in VF, the same oil can be used for upto 40 cycles of frying without quality deteoriation. Sensorial analysis revealed that VF chips retain a better colour, taste and flavour but were less crispy than that of AF chips. These findings validate the application of vacuum frying technology for the production of high-quality foods with lesser degradation of frying oil. Industrial relevance: Food manufacturers are now impelled by the health-conscious consumer base for the production of healthy food products. The toxic effect of foods fried in degraded oils on human health is now widely known and thus the production of safe fried foods is the need of hour globally. In this context, vacuum frying is the most feasible approach for the production of quality fried products retaining the natural colour, flavour, sensory and nutritional properties better than that of atmospheric frying. Vacuum frying causes the least degradation of fatty acid of the frying oil and the fried potatoes, producing healthy potato chips. Therefore, the oil used for vacuum frying have a greater shelf life and oxidative stability than atmospheric frying. However, the higher installation cost of vacuum fryer still limits its use in the street fried food market, where degradation of oil is more likely. Thus, for its widespread commercialisation in developing countries, steps should be taken both by government and manufacturing companies to reduce the installation costs. Highlights: Vacuum frying minimizes the PUFA degradation and minimize TFA formation compared with atmospheric frying. Vacuum fried chips retained better nutritional parameters. Vacuum fried chips show low oil content than atmospheric fried chips. Oxidative stability of frying oils was higher in vacuum frying compared to atmospheric frying. Vacuum frying technology produces high-quality foods with lesser degradation of frying oil.